PENGARUH KARAKTERISTIK PEKERJAAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI (Studi pada Balai Penelitian dan Pengembangan Agama Kementrian Agama) - Astuti, Sih Darmi; Subagyo, Herry; Adriyanto, Yeri (Benefit: Jurnal Manajemen dan Bisnis, 2011)
Current problem that often take place in the public sector is on how to improve employee performance. Employee performance will not be far from the three variables that examined in this study such as job characteristics, motivation, and organizational commitment. Research conducted at the Research and Development Centers of Religion, On Religion Ministry in Indonesia. The purpose of this current research is to examine the effect of job characteristics and motivation on organizational commitment and employee performance. In addition, the research aims to know the role of organizational commitment in mediating the relationship between job characteristics and motivation on employee performance. Data analysis using regression analysis and mediated regression analysis. In the first step data will be describe by using the qualification by the rating score and then will be continued with finding the significantly between the variable. Result concluded that only job characteristics that has not significant effect on employee performance. Furthermore, result also proved that organizational commitment has a mediating role in influencing the relationship between job characteristics and employee performance, but not for the relationship between motivation and employee performance. Based on research results, efforts to increase employee performance through job characteristics cannot ignore the organizational commitment aspect. The results implied that motivation of work was faster to improve the employee perfomance than job characteristics